(3JaSjQ GHf CHj MGJe GdQGRis - (3YHO GdQMef Hf eMeO CHj MGJe GHf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO,J (B327 (3g` s
(3ChdgG (B:s
(3jHOC HJaSjQ bhdg JYGdi (B:( (3Gde JYde Gf Gddg dg edc GdSehGJ hGdCQV (B) (3ShQI GdeGFOI hPdc Hbhdg (B: (3MOKfG Ydi Hf CHj hdGeI GdHZOGOi s
(3BNQgG (B:s
(3ai JaSjQ bhdg JYGdi (B( (3heG cGf Gddg eYPHge hge jSJZaQhf (B) (3ef ShQI GdGfaGd hPdc Hbhdg afSNJgG GdCjI GdJi JdjgG (B: ( (3heG dge GdGjYPHge Gddg hge jUOhf Yf GdeSLO GdMQGe (B) (3hGdMeO ddg QH GdYGdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B324 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B170s
(3JHUQGJ GdCUd (B:s
(3GdfSNI ebQhAI ef YGde eYQha (B: (3bQGAI HNW GdSjhWi SfI (B872s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs